The PI3K/AKT/mTOR pathway in scar remodeling and keloid formation: mechanisms and therapeutic perspectives - Liu, Jing; Yan, Junfei; Qi, Shengbin; Zhang, Jie; Zhang, Xin; Zhao, Yaping (Frontiers in Pharmacology, 2025)
Keloids and hypertrophic scars (HTS) represent aberrant wound healing characterized by excessive fibroblast activity and extracellular matrix accumulation. The PI3K/AKT/mTOR signaling pathway is vital in regulating these processes, promoting fibroblast proliferation, survival, and collagen synthesis. Dysregulation of this pathway, driven by genetic mutations, post-transcriptional modulation, and upstream signaling, contributes significantly to the pathogenesis of pathological scarring. This review collects current knowledge on the molecular mechanisms underlying PI3K/AKT/mTOR activation in keloids and HTS, highlighting the roles of key regulators such as PTEN, NEDD4, and non-coding RNAs. It also evaluates therapeutic strategies targeting this axis, including small-molecule inhibitors, natural compounds, and emerging delivery platforms. Targeting PI3K/AKT/mTOR offers a compelling avenue for developing effective, mechanism-based keloid and hypertrophic scarring treatments. The PI3K/AKT/mTOR signaling axis is central to these cellular mechanisms, which drive fibroblast proliferation, survival, myofibroblast transdifferentiation, and metabolic reprogramming (including suppressed autophagy and enhanced glycolysis.